Marketing Mix 7P Strategy Analysis At PT. Ayo Media Network Bandung - Arindya Putri Devina; Sam’un Jaja Raharja; Herwan Abdul Muhyi (Green Publisher Indonesia, 2024)
PT. Ayo Media Network Bandung is a company engaged in the digital mass media industry, offering a digital news portal product called AyoBandung.com. This research aims to obtain information and a real picture of how the implementation of the 7P marketing mix strategy is carried out by PT. Ayo Media Network Bandung in developing the AyoBandung.com product. The method used in this research is explorative qualitative, which concretely describes how the company implements the product, price, place, promotion, people, process, and physical evidence strategies. Data collection techniques for this research include interviews with 7 informants, documentation and literature studies, as well as source triangulation. The results of this research indicate that the company has implemented all elements of the marketing mix in its business marketing activities. However, not all elements are running optimally. The product, price, process, and physical evidence elements are functioning well. Meanwhile, the place, promotion, and people elements are still facing some obstacles.